UiTMLaw Webinar Series – Career Path Series - UiTM, Faculty of Law (Faculty of Law, 2020)
Webinar Series - Career Path Series was held on various topics, featuring the best panels, including What it Means to be a Corporate Lawyer, Legal Preneurship: I Come, I See, I Conquer, and The Pupillage Gateway.